Network pharmacology-based screening of the active ingredients and mechanisms of Cymbaria daurica against diabetes mellitus - Ruyu Shi; Dongxue Chen; Mingyue Ji; Baochang Zhou; Ziyan Zhang; Chunhong Zhang; Minhui Li (Food Science and Human Wellness)
Cymbaria daurica L. has a long history as a folk medicine and tea for the treatment of diabetes. However, the biological activity and mechanism of its hypoglycemic effect have not been fully elucidated. In this study, the potential mechanism of C. daurica against type 2 diabetes mellitus (T2DM) was postulated via pharmacological network analysis. Based on data mining techniques involving topological parameters, gene ontology, and pathway enrichment, we established a compound-target, protein-protein interaction, and target-pathway network to identify central targets and pathways. Pathway enrichment analysis revealed that the most important pathway associated with C. daurica in treating T2DM is the PI3K-Akt signaling pathway. Molecular docking was performed to validate the predicted results. Then, a HepG2 cell insulin resistance model and a high-fat, high-glucose diet combined with a streptozotocin-induced T2DM rat model was established to assess the fasting glucose changes and lipid profile after C. daurica treatment, respectively. Finally, real-time PCR and western blotting were used to verify changes in key targets. The anti-diabetic mechanism of the active ingredient in C. daurica may involve the regulation of IRS-2, Akt1, GLUT4, and GSK3β.